78.2k views
0 votes
3: (x+1) (x+3)

4: (y+6) (y+4)
5: (z-5) (z+3)
6: (a+8) (a-3)
7: (g-7) (g-2)
8: (n-6) (n-4)
9: (3m+1) (m+9)
10: (2p-4) (3p+2)
11: (6-5s) (2-s)

1 Answer

6 votes

(x+1)(x+3)=x^2+3x+x+3=x^2+4x+3\\\\(y+6)(y+4)=y^2+4y+6y+24=y^2+10y+24\\\\(z-5)(z+3)=z^2+3z-5z-15=z^2-2z-15\\\\(a+8)(a-3)=a^2-3a+8a-24=a^2+5a-24\\\\(g-7)(g-2)=g^2-2g-7g+14=g^2-9g+14\\\\(n-6)(n-4)=n^2-4n-6n+24=n^2-10n+24\\\\(3m+1)(m+9)=3m^2+27m+m+9=3m^2+28m+9\\\\(2p-4)(3p+2)=6p^2+4p-12p-8=6p^2-8p-8\\\\(6-5s)(2-s)=12-6s-10s+5s^2=5s^2-16s+12
User Benjamin Bihler
by
5.9k points